Antibiotic Resistance and Biofilm Production Capacity in Clostridioides difficile - Rahmoun, Layan Abu; Azrad, Maya; Peretz, Avi (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Clostridioides difficile (C. difficile) is one of the primary pathogens responsible for infectious diarrhea. Antibiotic treatment failure, occurring in about 30% of patients, and elevated rates of antibiotic resistance pose a major challenge for therapy. Reinfection often occurs by isolates that produce biofilm, a protective barrier impermeable to antibiotics. We explored the association between antibiotic resistance (in planktonic form) and biofilm-production in 123 C. difficile clinical isolates. Results: Overall, 66 (53.6%) out of 123 isolates produced a biofilm, with most of them being either a strong (44%) or moderate (34.8%) biofilm producers. When compared to susceptible isolates, a statistically higher percentage of isolates with reduced susceptibility to metronidazole or vancomycin were biofilm producers (p < 0.0001, for both antibiotics). Biofilm production intensity was higher among tolerant isolates; 53.1% of the metronidazole-susceptible isolates were not able to produce biofilms, and only 12.5% were strong biofilm-producers. In contrast, 63% of the isolates with reduced susceptibility had a strong biofilm-production capability, while 22.2% were non-producers. Among the vancomycin-susceptible isolates, 51% were unable to produce biofilms, while all the isolates with reduced vancomycin susceptibility were biofilm-producers. Additionally, strong biofilm production capacity was more common among the isolates with reduced vancomycin susceptibility, compared to susceptible isolates (72.7% vs. 18.8%, respectively). The distribution of biofilm capacity groups was statistically different between different Sequence-types (ST) strains (p =0.001). For example, while most of ST2 (66.7%), ST13 (60%), ST42 (80%) isolates were non-producers, most (75%) ST6 isolates were moderate producers and most of ST104 (57.1%) were strong producers. Conclusions: Our results suggest an association between reduced antibiotic susceptibility and biofilm production capacity. This finding reinforces the importance of antibiotic susceptibility testing, mainly in recurrence infections that may be induced by a strain that is both antibiotic tolerant and biofilm producer. Better adjustment of treatment in such cases may reduce recurrences rates and complications. The link of biofilm production and ST should be further validated; if ST can indicate on isolate virulence, then in the future, when strain typing methods will be more available to laboratories, ST determination may aid in indecision between supportive vs. aggressive treatment.